Development of a 3D Printed Lung Model Made of Synthetic Materials for Simulation - Liu, Ganwei; Bian, Wenjie; Zu, Guili; Liu, Jing; Zhang, Guoxin; Li, Changji; Jiang, Guanchao (The Thoracic and Cardiovascular Surgeon, 2021)
Background Considering the complexity of lung structures and the difficulty of thoracoscopic surgery, simulation-based training is of paramount importance for junior surgeons. Here, we aim to design a high-fidelity lung model through utilizing the three-dimensional (3D) printing technology combined with synthetic materials to mimic the real human lung.Methods The 3D printed lung model was manufactured based on the computed tomography images of a randomly selected male patient. Synthetic materials were used for the construction of lung parenchyma, blood vessels, and bronchi. Then, the model was assessed in terms of its visual, tactile, and operational features by participants (the senior surgeons, junior surgeons, and medical students), who were asked to complete the specially designed survey-questionnaires.Results A 3D printed model of the right lung made of synthetic materials was successfully fabricated. Thirty subjects participated in our study (10 senior surgeons, 10 junior surgeons, and 10 medical students). The average visual evaluation scores for senior surgeons, junior surgeons, and medical students were 3.97 ± 0.61, 4.56 ± 0.58, 4.76 ± 0.49, respectively. The average tactile evaluation scores were 3.40 ± 0.50, 4.13 ± 0.68, 4.00 ± 0.64, respectively. The average operation evaluation scores were 3.33 ± 0.83, 3.93 ± 0.66, 4.03 ± 0.66, respectively. Signiﬁcant lower scores were obtained in the group of the senior surgeons compared with the other two groups.Conclusion A high level of fidelity was exhibited in our 3D printed lung model and it could be applied as a promising simulator for the surgical training in the future.
Keywords: 3D printed lung model; synthetic materials; fidelity; surgical training; thoracoscopic surgery